Smoking in adolescents: The effect of academic stress and smoking self-efficacy - Astuti, Kamsih; Waseso, Aldhiyunfikar Purbo (Universitas Mercu Buana Yogyakarta, 2023)
Although smoking is a harmful habit, a considerable number of people smoke, especially young people. Adolescents are encouraged to smoke for many reasons. The objective of this study was to evaluate the relationship between teenage smoking self-efficacy and academic stress prediction. One hundred adolescents who smoked served as the subjects. The smoking behavior scale, the academic stress scale, and the smoking self-efficacy scale were the tools used in this investigation. Multiple regression analysis was used to examine the data. Multiple linear regression analysis results indicated that smoking self-efficacy and academic stress have a significant predictive relationship with smoking behavior. This variable has a coefficient of determination of 28.8%. Stress from school has a lower contribution than smoking self-efficacy. Therefore, increasing smoking self-efficacy through improved emotional regulation skills and assertiveness when declining offers to smoke can help reduce adolescent smoking behavior. In addition, teaching teenagers how to adaptively handle their academic stress will prevent them from turning to smoking or cigarettes as a coping mechanism.